UNUSUAL PRESENTATION OF PULMONARY SARCOIDOSIS - Antonijevic, Gordana; Stanojevic, Dragan; Opancina, Valentina (Medicinski časopis, 2018)
Sarcoidosis is a systemic granulomatous disease of unknown etiology, with ambiguous presentation. Pulmonary sarcoidosis is rare and its presentation is untypical. In this paper we present a case of pulmonary sarcoidosis with unspecific presentation. In 1995, a 36 year old pilot presented with no previous history of any notable illness and without symptoms. Chest radiography showed lesion and Ziehl-Neelsen staining showed the presence of acid-resistant bacteria, after which antituberculotic therapy started. After multiple hospitalizations, in 2011, radiography showed changes in lungs that remind of sarcoidosis or tuberculous sequelae. In 2016, tuberculosis was excluded and revised pathohistological findings of granulomatous inflammation in 2003, clinical presentation and radiography findings suggested sarcoidosis with slow progression and fibrous indurative changes in upper lung lobes with the presence of low grade lymphocyte alveolitis.